2009
DOI: 10.1002/cbm.741
|View full text |Cite
|
Sign up to set email alerts
|

Recorded incidents in a high‐secure hospital: A descriptive analysis

Abstract: These findings can inform prevention and management of violence and self-harm. Dealing with such a large number of incidents is time consuming, even if they are not especially serious. Attention to environmental, as well as individual, issues is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 14 publications
(20 reference statements)
6
39
1
Order By: Relevance
“…Few studies have thus far described incidents while in forensic care (e.g. Uppal et al 123 ), although recent behaviour within institutions might arguably be at least as important as previous offending in determining future placement, in particular for those whose index offences are many years, sometimes decades, in the past. Others have found that need for seclusion 81 and absonsion and aggression 79 during admission are associated with longer LoS.…”
Section: Offending and Riskmentioning
confidence: 99%
“…Few studies have thus far described incidents while in forensic care (e.g. Uppal et al 123 ), although recent behaviour within institutions might arguably be at least as important as previous offending in determining future placement, in particular for those whose index offences are many years, sometimes decades, in the past. Others have found that need for seclusion 81 and absonsion and aggression 79 during admission are associated with longer LoS.…”
Section: Offending and Riskmentioning
confidence: 99%
“…Self-harm incidents as a service-level outcome indicator were reported in only two studies. 59,62 Neither of these studies reported change over time in self-harm as a result of intervention at the service level.…”
Section: Reoffending/'offending-like' Behaviour/incidentsmentioning
confidence: 99%
“…In addition, patients presenting to accident and emergency (A&E) departments are 'treatment seekers' and therefore motivated to seek help at the time of the act. On the other hand, patients in secure institutions often self-harm in secret (Uppal 2009): they tend to use high-risk methods of self-harm and often refuse to be helped. The risk of assaults on staff by patients when they try to prevent and manage such acts is well known (Uppal 2009), with a major impact on staff morale and capacity to care (Howard League of Penal Reforms 2003).…”
Section: Self-harm and Suicide In Prisons And Secure Hospitalsmentioning
confidence: 99%
“…On the other hand, patients in secure institutions often self-harm in secret (Uppal 2009): they tend to use high-risk methods of self-harm and often refuse to be helped. The risk of assaults on staff by patients when they try to prevent and manage such acts is well known (Uppal 2009), with a major impact on staff morale and capacity to care (Howard League of Penal Reforms 2003). Finally, in most cases, no one other than the patient is responsible for the…”
Section: Self-harm and Suicide In Prisons And Secure Hospitalsmentioning
confidence: 99%